2010
DOI: 10.1161/circulationaha.109.934950
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Characteristics, and Outcomes of Patients Presenting With Cardiogenic Unilateral Pulmonary Edema

Abstract: Background-Cardiogenic unilateral pulmonary edema (UPE) is a rare entity, frequently leading to initial misdiagnosis.We sought to assess the prevalence of UPE and to determine its impact on prognosis compared with bilateral pulmonary edema. Methods and Results-We studied the characteristics and outcomes of patients admitted to our institution for cardiogenic pulmonary edema during an 8-year period. The study population included 869 consecutive patients. The prevalence of UPE was 2.1%: 16 right-sided UPE (89%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 33 publications
4
77
2
4
Order By: Relevance
“…Nevertheless, in patients admitted to critical care areas—such as in our study—hospital mortality is higher (32%), at least in the only reported series that involved 199 patients 24. In our work, hospital mortality was somewhat lower (25%), but it was higher than in patients not admitted to critical care areas,7, 10, 18, 22, 23 likely because of the more severe respiratory and/or hemodynamic condition, as indicated by the high need for endotracheal intubation or inotropic agents (26% and 29%), respectively. Another possible explanation was the high proportion of de novo cases of APE (>80%), a fact that has also been associated with higher hospital mortality 20.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Nevertheless, in patients admitted to critical care areas—such as in our study—hospital mortality is higher (32%), at least in the only reported series that involved 199 patients 24. In our work, hospital mortality was somewhat lower (25%), but it was higher than in patients not admitted to critical care areas,7, 10, 18, 22, 23 likely because of the more severe respiratory and/or hemodynamic condition, as indicated by the high need for endotracheal intubation or inotropic agents (26% and 29%), respectively. Another possible explanation was the high proportion of de novo cases of APE (>80%), a fact that has also been associated with higher hospital mortality 20.…”
Section: Discussioncontrasting
confidence: 48%
“…In patients with APE, in‐hospital mortality seems comparable to patients with acute heart failure ranging also from 7.4% to 17%,7, 10, 18, 22, 23 although in small and earlier reports,7, 18 mortality was higher (12% and 17%) than in larger, more recent studies (7.4%–9.6%) 10, 22, 23. Nevertheless, in patients admitted to critical care areas—such as in our study—hospital mortality is higher (32%), at least in the only reported series that involved 199 patients 24.…”
Section: Discussionmentioning
confidence: 95%
“…Attias et al . reported that unilateral pulmonary edema represents approximately 2% of cardiogenic pulmonary edema 3. The most common cause of unilateral pulmonary edema is severe mitral regurgitation, as in our two cases 3.…”
Section: Discussionsupporting
confidence: 58%
“…reported that unilateral pulmonary edema represents approximately 2% of cardiogenic pulmonary edema 3. The most common cause of unilateral pulmonary edema is severe mitral regurgitation, as in our two cases 3. Unilateral cardiogenic pulmonary edema is often misdiagnosed as pneumonia, aspiration, or alveolar hemorrhage 4.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation